Symposium 4: Engaging with International Students: An Account of practice In On-line Assessment - Trehan, Kiran (Proceedings of the International Conference on Networked Learning, 2008)
Increasing attention is focusing on the value of Critical approaches to enhancing networked learning (Hodgson & Fox, 1995, McConnell, 1999, Trehan &Reynolds, 2002). This paper examines how Critical on-line assessment and psychoanalytic processes can be harnessed to produce valuable insights into some of the social processes involved in collaborative assessment and challenges, the implicit assumption that such practices necessarily bring about equality. Interculturality and diversity in student groups influence power relations, which in turn are likely to affect the process of on-line collaborative assessment and its outcome. Psychodynamic perspectives not only explore underlying power and control issues but also actively engage in an examination of political and Inter- cultural processes affecting the development process. Such perspectives provide an opportunity to participate creatively in a collaborative sense making process, where understanding emerges by experimentation and through engagement with diversity and intercultural perspectives. Psychodynamics and Interculturality The interplay between psychodynamic approaches and network learning provides an opportunity to explore collaborative assessment at an individual, group and community level as conscious and unconscious processes. Psychodynamic perspectives illuminate approaches that differentiate between behaviours and activities geared toward rational task performance and those geared to emotional needs and anxieties. The application of this approach emphasises the importance of understanding human relationships through the idea of connectedness and relatedness. In doing so, the emphasis is placed on "learning from the conscious and unconscious levels of connection that exist between the self and others, people and systems" (French & Vince, 1999, p7). To develop our understanding of Interculturality within collaborative assessment, we need to find ways of exploring the nature of authority, the exercise of authority and power, the relationship of individuals and the learning communities to their social, political, cultural and economic environment. We also need to examine how emotions (e.g. humour, fear, anxiety) reverberate on the relational nature of collaborative assessment and impact on the International student community. Applying psychodynamic ideas to collaborative assessment means not just exploring assumptions of power and control but actively engaging in an examination of political and cultural processes that Impact on the learning process in an intercultural context. Another critical aspect of psychodynamic theory to the study of on-line assessment is the interrelation between emotions and International community dynamics. Emotions and the study of the International learning community are central to psychodynamic theory because it reveals emotions as the prime medium through which people act and interact. The intended contribution of this paper is to explore and identify ways in which the interplay between on-line collaborative assessment and psychodynamics can provide an opportunity to evaluate and reflect on the relevance and impact of Interculturality within the learning process. In doing so, I am proposing an approach that illuminates the quietly spoken aspects of Interculuraltity as a backdrop for unveiling the hypocrisies and contradictions of engaging in on-line collaborative assessment, which can create Isolation, exclusion and discrimination in programmes that encompass students from a variety of International cultures.